2014 11th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technolo 2014
DOI: 10.1109/ecticon.2014.6839757
|View full text |Cite
|
Sign up to set email alerts
|

The classification flesh aromatic coconuts in daylight

Abstract: The purpose of this paper was to develop an efficient and accurate classification for flesh aromatic coconuts in daylight by using image processing technique. In actual implementation , the brightness of daylight was not constant as a major problem that is affecting for the classification flesh aromatic coconuts. So we need to adjust the brightness of image to have the same brightness in all images before to be classify flesh aromatic coconut. The color of the coconut's rind around the bottom of aromatic cocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To provide an accurate identification of maturity of aromatic coconut fruit without opening them, image processing technology has been developed [54,55]. This identification process is based on mathematical correlations between the fruit's morphology and the percentage of white pixels formed on the image.…”
Section: Utilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide an accurate identification of maturity of aromatic coconut fruit without opening them, image processing technology has been developed [54,55]. This identification process is based on mathematical correlations between the fruit's morphology and the percentage of white pixels formed on the image.…”
Section: Utilisationmentioning
confidence: 99%
“…The precision of the technique is significantly improved under natural lighting conditions. It was shown that the classifying power of this system could achieve an accuracy of at least 77% in identifying aromatic fruit [55].…”
Section: Utilisationmentioning
confidence: 99%
“…The Raspberry Pi products as a cheap microprocessor have now been used for applications that utilize neural networks (Monteiro, 2018). Its capabilities for image processing have been proven of good use when it comes to feature extraction and classification in coconut based on this technique has been made (Arboleda et al, 2020;Tantrakansakul & Khaorapapong, 2014). Studies centered in coconut researches find its way to the realm of machine learning techniques to determine its quality (Alonzo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%